Internal environmental displacement: a growing challenge to the United States welfare state - Meyer, Michelle A. (Oñati Socio-Legal Series, 2013)
While the greatest potential for environmental displacement occurs in poorer nations, internal displacement has resulted from environmental change and disasters in the United States; and climate change will likely amplify this movement. I describe how environmental displacement is a policy drift that reduces the effectiveness of current welfare state policies to protect US populations from the risk of impoverishment. Evidence from previous disasters indicates environmental displacees have particular assistance needs. I identify the four main assistance needs in my Environmental Displacement and Resilience Model then use this model to evaluate whether current policies address housing, finances, health, and discrimination needs of those displaced. My analysis highlights a gap between the country’s response to disasters and the current welfare state social safety nets. Without disaster and welfare policy changes environmental displacement will continue to be a policy drift that leave displacees vulnerable to social and economic marginalization.